Mania associated with self-prescribed acetyl-l-carnitine in a man with bipolar I disorder. (February 2017) - Goodison, Geraldine; Overeem, Kathie; de Monte, Veronica; Siskind, Dan
Objective: Complementary medicines are readily available and becoming increasingly popular. Acetyl-l -carnitine (ALC) is widely recognised as a safe dietary supplement to aid weight loss. We present the case of a patient who had a relapse of mania in the context of ALC use for weight loss over a two week period, on the background of bipolar I disorder previously in remission. The patient's symptoms resolved a few days after ALC was ceased. Conclusions: Given the high rates of obesity among people with mental illness, it is possible ALC may be utilised in the hope of aiding weight loss. This case highlights the importance of psychiatrists maintaining open communication with their patients about use of complementary medicines, and the risks and benefits of their use.